Surface ZnSe:Ca layers with hole conductivity - Makhniy, V.P.; Berezovskiy, M.M.; Kinzerska, O.V.; Melnyk, V.V. (Технология и конструирование в электронной аппаратуре, 2019)
The authors investigate the effect of treating n-ZnSe substrates with boiling aqueous Ca(NO₃)₂ suspension on their electrical and luminescent properties. Base substrates were cut from bulk pure zinc selenide crystals grown from a stoichiometric melt by the Bridgman method. It was found that the Ca-doping of the substrates causes an almost complete “quenching” of the low-energy orange emission band with a maximum near hωmax ≈ 1,95 eV and a significant increase in the efficiency of the edge blue luminescence band. Исследовано влияние обработки подложек n-ZnSe в кипящей водной суспензии соли Ca(NO₃)₂ на их элек-трические и люминесцентные свойства. Досліджено вплив обробки підкладинок n-ZnSe в киплячій водній суспензії солі Ca(NO₃)₂ на їхні електричні та люмінесцентні властивості.